Analisis Pertanggungjawaban Pidana terhadap Anak di bawah Umur sebagai Pelaku Pembunuhan Berencana - Cindy Aura Cahyani (LP3M Sekolah Tinggi Ilmu Hukum Al-Banna, 2025)
Premeditated murder is a serious crime that raises specific issues when committed by a child, particularly in relation to criminal responsibility and sentencing restrictions in the juvenile justice system. This study analyzes the criminal responsibility of children as perpetrators of premeditated murder based on the Criminal Code and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA Law). The method used is normative legal research with a regulatory, conceptual, and case approach through the examination of norms and relevant court decisions. The results of the study show that children can be held criminally responsible as long as they meet the age requirements and the elements of guilt and premeditated murder can be legally proven. However, the process and punishment of children are subject to a special regime that emphasizes child protection, rehabilitation, and punishment as a last resort (ultimum remedium), with restrictions on the type of sanctions and the length of punishment in accordance with the provisions of the UU SPPA. Thus, the application of the norms of the Criminal Code and the UU SPPA in court decisions needs to ensure a balance between legal certainty, a sense of justice, and the goal of child development.